2008
DOI: 10.1007/s00253-008-1401-x
|View full text |Cite
|
Sign up to set email alerts
|

Action of antimicrobial substances produced by different oil reservoir Bacillus strains against biofilm formation

Abstract: Microbial colonization of petroleum industry systems takes place through the formation of biofilms, and can result in biodeterioration of the metal surfaces. In a previous study, two oil reservoir Bacillus strains (Bacillus licheniformis T6-5 and Bacillus firmus H(2)O-1) were shown to produce antimicrobial substances (AMS) active against different Bacillus strains and a consortium of sulfate-reducing bacteria (SRB) on solid medium. However, neither their ability to form biofilms nor the effect of the AMS on bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 23 publications
1
24
0
2
Order By: Relevance
“…[8, 17]. Our observation on the heat-stability profile and resistance to enzymes was also supported by a highly heat-stable (100°C for 1 h) antibacterial peptide produced by a Brazilian oil isolate Bacillus firmus H 2 O-1 that was found to be resistant to proteases and was stable at alkaline pH [25]. Chemical treatments with surfactants, metal salts, and EDTA did not cause any adverse effect on biological activity.…”
Section: Discussionmentioning
confidence: 54%
“…[8, 17]. Our observation on the heat-stability profile and resistance to enzymes was also supported by a highly heat-stable (100°C for 1 h) antibacterial peptide produced by a Brazilian oil isolate Bacillus firmus H 2 O-1 that was found to be resistant to proteases and was stable at alkaline pH [25]. Chemical treatments with surfactants, metal salts, and EDTA did not cause any adverse effect on biological activity.…”
Section: Discussionmentioning
confidence: 54%
“…Some studies have demonstrated that these species are hydrocarbon degraders, and one strain of B. firmus has already been isolated from oil reservoirs (Korenblum et al 2008). Crawford (1975) report that B. megaterium is able to use 2-chlorobenzene as a substrate.…”
Section: Dominant Microbial Community Evolution During Treatment Perimentioning
confidence: 99%
“…Bacteriocin from Bacillus species are of interest because of their broader range of activity including Gram negative bacteria and fungi [27]. Bacteriocin like inhibitory substance from Bacillus species has been reported for its antimicrobial activity and antibiofilm potential [28]. Sonorensin, a bacteriocin isolated from marine isolate Bacillus sonorensis, has exhibited S. aureus biofilm inhibition and since it could target both multiplying and non-multiplying bacteria, the resistance could not be developed against it [29].…”
Section: Molecular Characterization Of Potential Candidatementioning
confidence: 99%